Pola Pemberatan Ancaman Pidana Berbasis Konservasi Lingkungan Hidup: Kajian Atas Undang-Undang di Bidang Lingkungan Hidup - mahrus ali (UIN Sunan Kalijaga Yogyakarta, 2012)
The severity model and orientation of threat of punishment in some environmentacts have not been directed to protection of environment. There are two ways to haveenvironment based severity model of threat of punishment. First, the severity model ofthreat of punishment ranges from punishment to treatment or from certain kind oftreatment to other. Second, in term of fine imposed to defendent the severity model ofthreat punishment is based on multiplicity of fine